Increasing Hispanic Heritage Language Learners’ Motivation for Learning Spanish in a Foreign Language Classroom by Differentiating the Content and Validating their Identity - Flores-Whitinger, Elena (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
As there are an increasing number of Hispanic students entering the U.S. school system, middle and high school Spanish teachers have been presented with the issue of creating curriculums that challenge both Foreign Language Learners (FLLs) and Heritage Language Learners (HLLs). Hispanic students who enroll in FLL Spanish classes are categorized as HLLs and range from novice to native in their proficiency levels. If Spanish teachers are able to differentiate for their students and integrate them into the classroom in a way that is beneficial for both HLLs and FLLs then perhaps the HLLs will begin to see the benefits of maintaining both their Spanish and their English literacy skills.